PELATIHAN PEMBUKUAN SEDERHANA UMKM BERBASIS MICROSOFT EXCEL PADA CV. ADI SANJAYA SEJAHTERA KOTA MADIUN - Puji Nurhayati; Juli Murwani; Rihan Mustafa Zahri; Anisa Prima Dihastuti; Vannesa Ghifarianty (Universitas PGRI Madiun, 2022)
Micro, Small and Medium Enterprises (MSMEs) play an important role in the Indonesian economy. In fact, MSMEs face various obstacles or problems caused by several factors, namely: low education, lack of understanding of information technology, and lack of reliability of financial statement characteristics. The purpose of this community service activity is to provide training to CV. Adi Sanjaya Sejahtera on simple bookkeeping using Microsoft Excel according to SAK MSME standards. The implementation of this activity is divided into preliminary surveys, tutorials and simple bookkeeping training practices, and evaluations. At the preliminary survey stage before community service was carried out, it was found that CV. Adi Sanjaya Sejahtera still does the bookkeeping using a manual book so it is less efficient to compile financial reports. The number of participants in the activity is 2 people who are owners and employees of CV. Adi Sanjaya Prosperous. The activity went smoothly and the participants were very enthusiastic. The results of this community service are expected CV. Adi Sanjaya Sejahtera can improve his ability and knowledge in simple bookkeeping and preparation of financial reports in accordance with financial accounting standards and provide quality financial report information using Microsoft excel.